Probing the stellar initial mass function with high-[zeta] supernovae - Souza, Rafael S. de; Ishida, E. E. O.; Whalen, Daniel J.; Johnson, J. L.; Ferrara, A. (Monthly notices of the Royal Astronomical Society, 2014)
Abstract. The first supernovae (SNe) will soon be visible at the edge of the observable universe, revealing the birthplaces of Population III stars. With upcom